Teeth processing in human teeth bank – proposal of protocol - Lucimara Albrecht; Erica Lopes Ferreira; Maria Luiza Minuzzi Passos; Rossana Tais Cecchetti (Revista Sul-Brasileira de Odontologia, 2014)
Dentistry courses conduct preclinical laboratory trainings and research using extracted human teeth. For a safe usage of those teeth, it is necessary to subject them to cleaning, disinfection and/or sterilization and proper storage to ensure they are free of biological residues. Each of these steps should be properly described in standard operating procedures (SOPs) and in the processing protocol of the Human Tooth Bank (HTB). Objective: To create a processing protocol for Human Tooth Bank based on a literature review on cleaning, disinfection and/or sterilization and storage methods for extracted human teeth. Literature review: The hand hygiene and use of personal protective equipment are essential at all stages of processing. The previous cleaning of the tooth is essential, preferably with enzymatic detergent, and complemented by ultrasonic washing machine. The water quality should be considered in cleaning, washing, dilution of the enzymatic detergent and in the ultrasonic washing machine. Due to the prohibition of immersion use of chemical solution as sterilizing agents, saturated steam under pressure is widely used. Freezing is the recommended storage method because neither it alters dental structures nor affects research results. All this information should be consider for the elaboration of the processing protocol for extracted human teeth. Each action taken requires a detailed description and must be validated by the institution. Conclusion: The adoption of a protocol with SOPs for cleaning, disinfecting and/or sterilization and storage of human teeth in HTB standardize the processing and minimize exposure to biological agents, enabling the use of the tooth under appropriate conditions for research and laboratory preclinical training.